2021
DOI: 10.3390/ani11113255
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Histologic Effects of Visible Implant Elastomer (VIE) and Passive Integrated Transponder (PIT) Tags in the Marine Toad (Rhinella marina)

Abstract: Passive integrated transponder (PIT) and visible implant elastomer (VIE) tags are commonly used to identify reptiles, amphibians, and fish. Despite reports of good retention rates and little to no negative effect on survival time, migration remains a concern and histologic changes have not been widely evaluated. Fifty-six wild-caught marine toads (Rhinella marina) were marked with a PIT tag in the left caudal thigh and a VIE tag over the right gastrocnemius muscle prior to transport to the North Carolina Zoo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Critical studies of their impacts have revealed real and potential impacts on individual performance and survival (Bloch & Irschick 2005 ; Narayan et al 2011 ). Marking may directly reduce survival through physical impairment (Bloch & Irschick 2005 ), for example, how improperly cured elastomer can migrate to organs where it can presumably impair organ function (McCarthy & Parris 2004 ; Cabot et al 2021 ). Even when no physical impairment occurs, marking may elicit behavioural responses immediately post-marking that have the potential to mediate downstream welfare and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Critical studies of their impacts have revealed real and potential impacts on individual performance and survival (Bloch & Irschick 2005 ; Narayan et al 2011 ). Marking may directly reduce survival through physical impairment (Bloch & Irschick 2005 ), for example, how improperly cured elastomer can migrate to organs where it can presumably impair organ function (McCarthy & Parris 2004 ; Cabot et al 2021 ). Even when no physical impairment occurs, marking may elicit behavioural responses immediately post-marking that have the potential to mediate downstream welfare and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Critical studies of their impacts have revealed real and potential impacts on individual survival. Marking may directly reduce survival through physical impairment, for example how improperly cured elastomer can migrate to organs where it can presumably impair organ function (Cabot et al 2021; McCarthy & Parris 2004). Even when no physical impairment occurs, marking may elicit behavioural responses immediately post-marking that have the potential to mediate downstream welfare and survival.…”
Section: Introductionmentioning
confidence: 99%